PENGOLAHAN MOTIF MENGGUNAKAN TEKNIK ROTATION ESCHER DENGAN INSPIRASI RAGAM HIAS KAIN BATIK MADURA - Latifah, Rania Nurul; Rosandini, Morinta (Jurnal Dimensi Seni Rupa dan Desain, 2023)
Developments in making motifs are very diverse in form and technique; in processing motifs, repetition techniques are needed, one of which is the tessellation repetition technique. Tessellation is creating a two-dimensional plane using geometric elements that are repeated without gaps and overlaps. Dutch graphic artist Maurits Cornelis successfully created tessellation using non-geometric shapes. It has four techniques in its manufacture: translation, reflection, rotation, and glide reflection. Previous studies have carried out the development of the rotation Escher technique with the inspiration of Indonesian fabrics. Still, the results of processing the motifs have not been optimal. So that further research is needed with proper processing to be able to produce more diverse motifs. The Escher rotation technique has special mathematical calculations and uses a different basic form. This study aims to create variations of non-geometric plane motif modules with tessellation compositions using the Escher rotation technique. This study brings Madura batik motifs that also have organic visual similarities and are geometric patterns with the Escher tessellation technique to provide more aesthetic value to the motif work. This study uses a qualitative method by conducting a literature study on the theory of rotation Escher, visual observation of objects in the rotation Escher technique, and Madura Batik fabrics. The next step is to process the motifs digitally using the Escher rotation technique with the inspiration of Madura Batik cloth. The final result is a variation in the shape of the motif in the form of a modification of the Escher rotation technique with visual details of the flora of chickens, peacocks, birds, fish, and flowers to have local content. This variety of motif creations can be used as a visual reference for designers to make motif applications on clothing.Keywords: Batik, Escher, Geometric, Madura, Motive, Tessellation.